Enhancement of neuroprotection, antioxidant capacity, and water-solubility of crocins by transglucosylation using dextransucrase under high hydrostatic pressure - Mok, Il-Kyoon; Thi Thanh Hanh Nguyen; Kim, Dong Hoi; Lee, Jae Wook; Lim, Sangyong; Jung, Ho-Yong; Lim, Taeyun; Pal, Kunal; Kim, Doman (ELSEVIER SCIENCE INC, 2020)
Crocin, one of the major carotenoid pigments of Crocus sativus (saffron), is responsible for antioxidant activity, neuroprotection, and the inhibition of tumor cell proliferation. In order to improve the functionality of crocin, alpha-glucosyl-(1 -> 6)-trans-crocins (C-Gs) were synthesized using sucrose and dextransucrase from Leuconostoc mesenteroides. High hydrostatic pressure (HHP) technique was applied to the synthesis process of C-Gs in order to improve its transglucosylation yield. A 100 MPa HHP condition enhanced the production yield of C-Gs by 1.95 times compared to that of 0.1 MPa atmospheric pressure. Novel C-Gs were purified by HPLC, and their chemical structures were determined using NMR analysis. Novel C-Gs increased water solubility 4.6-5.7 times and antioxidant activity 1.5-2.6 times, respectively, compared to crocin, and their neuroprotections (cell viability 92.5-100.4 %) on HT22 mouse hippocampal neuronal cells were significantly higher than that of crocin (cell viability 84.6 %). This advanced neuroprotection of novel C-Gs could be highly associated with their enhanced antioxidant activity. Thus, the enhanced water solubility and functionality of novel C-Gs can induce better clinical efficacy of neuroprotection than trans-crocin.
Keywords: CROCETIN; ABTS; CAROTENOIDS; STABILITY; PREVENTS; BEHAVIOR; SAFFRON; EXTRACT; DEATH; DPPH